Five years of national airborne pollen monitoring in South Africa: biome-specific calendars to inform allergy diagnosis and prevention - Takudzwa Matuvhunye; Dilys M. Berman; Nanike Esterhuizen; Andriantsilavo H. I. Razafimanantsoa; Frank H. Neumann; Dorra Gharbi; Keneilwe Podile; Tshiamo Mmatladi; Boitumelo Langa; Moteng E. Moseri; Linus Ajikah; Angela Effiom; et al. (Aerobiologia, 2026)
Pollen monitoring is crucial for understanding seasonal patterns, supporting allergy diagnosis and informing early warning tools to mitigate allergic diseases. The Southern Hemisphere lacks long-term pollen seasonal data, with extremely few records from Africa. We present pollen calendars based on five years of data from South Africa. Airborne pollen from 2019 to 2024 across South African biomes was collected in seven cities using Hirst-type volumetric spore traps and standard protocols. Daily concentrations were analysed by light microscopy. The five-year mean annual pollen integral (APIn) were calculated for each site. The five-year mean APIn was highest in the Grassland Biome (Bloemfontein) and lowest in the Albany Thicket Biome (Gqeberha). The Grassland Biome (Johannesburg) had the highest average tree pollen integral, while the Savanna Biome (Kimberley) had the highest average annual grass pollen integral. The grass family (Poaceae ) was the most common pollen type across all biomes. Other common taxa were exotic trees Cupressaceae, Platanus , Morus and Betula . Tree seasons were July to September, while grass and weed pollen seasons varied across the biomes. These five-year pollen calendars provide the first biome-specific national reference for airborne pollen exposure in South Africa. The findings provide baseline data for the clinical management of allergic disease.

Temperature, trophic state, and carrying capacity govern pelagic size spectra in the Atlantic Ocean - Ralf Schwamborn; Tim Dudeck; Claire Carré; Gabriel Bittencourt Farias; María Couret; Javier Díaz-Pérez; Mathilde Dugenne; Gabriela Guerra Araújo Abrantes de Figueiredo; Thierry Frédou; Flávia Lucena-Frédou; Xiomara F.G. Díaz; Dawit Yemane; et al. (Progress in Oceanography, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Development and analysis of a SmPC-based machine-readable dataset of contraindications for clinical decision support and real-world data analysis - Miriam Schechner; Wahram Andrikyan; Thomas Bauerdick; Theresa Terstegen; Louisa Redeker; Martin Federbusch; Katrin Farker; Alexander Strübing; Florian Schmidt; Petra Thürmann; Sven Schmiedl; Hanna M. Seidling; et al. (European Journal of Clinical Pharmacology, 2026)
Purpose Unrecognized contraindications pose risks for adverse drug reactions, hospitalizations or death. Clinical decision support systems (CDSS) aim to mitigate medication-related harm, particularly originating from contraindications. However, many CDSS provide limited benefit, as they focus largely on singular risk situations such as drug-drug interactions and often generate alerts of limited clinical relevance. Comprehensive integration of contraindications into CDSS may support more clinically meaningful alerts. The aim of this work was the development and analysis of machine-readable contraindication lists, including drug-clinical condition, drug-kidney function and drug-drug (group) contraindications, for integration into CDSS and real-world data analysis. Methods We extracted and operationalized contraindications, based on Summaries of Product Characteristics (SmPCs), of the 688 most prescribed drugs in Germany, leveraging common medical coding systems. Moreover, we analyzed extracted contraindications based on operationalizability, overall frequency and frequencies within different contraindication categories. Results In total, we extracted 4676 contraindications, of which 2129 (45.5%) were deemed operationalizable. Of these 2129 contraindications, 1652 (77.6%) were attributed to drug-clinical condition, 83 (3.9%) to drug-kidney, 140 (6.6%) to drug-drug group and 254 (11.9%) to drug-drug. The most frequently mentioned contraindicated risk situations were ‘severe liver insufficiency’ ( n = 74, 3.5%), ‘pregnancy’ ( n = 66, 3.1%), ‘MAO-inhibitors’ ( n = 44, 2.1%), and ‘shock’ ( n = 44, 2.1%). Conclusion Our results show, that drug-clinical condition contraindications are listed far more frequently in SmPCs than other contraindication categories. Focusing on clinical condition-related contraindications within CDSS could improve the detection of clinically relevant contraindications in routine data and enhance medication safety. The clinical applicability is currently being evaluated in the INTERPOLAR study.

Temperate Forest Floors: Ecosystem Hubs in Transition? - Friederike Lang; Jörg Prietzel; Frank Hagedorn; Klaus Kaiser; Stefanie Schulz; Mathias Mayer; Lars Vesterdal; Jürgen Bauhus; Maï Bergmann; Sebastian Bibinger; Martin I. Bidartondo; Jingxuan Olivia Chen; et al. (Global Change Biology, 2026)
The forest floor (FF) plays a key role in carbon, nutrient, and water cycling. It is the biologically most active compartment of forest soils, highly responsive to environmental conditions. Yet, its response to current changes in environmental conditions and forest management is understudied. Temperate forests are among the best studied ecosystems globally, providing the necessary ecological and biogeochemical background information to assess FF changes. Here, we focus on identifying existing knowledge and gaps in our understanding of the functioning of the FF. Interactions between FF biota and abiotic FF components show multifactorial dependencies with environmental conditions and drive FF turnover. Vice versa, the turnover of FF regulates carbon, nutrient, and water cycling. With slow litter decomposition and limited bioturbation, organic matter accumulates, nutrients cycle tightly within the FF, and water passes through this layer partly along preferential pathways. With rapid litter decomposition and intense bioturbation, FF accumulation is little, the mineral soil is the main nexus for plant nutrient uptake and organic matter transformation, and water infiltrates the mineral soil more homogeneously. The interconnectedness with the adjacent ecosystem compartments is a crucial feature of the FF, feeding back to its functioning and making it a central hub of forest processes. The FF morphology reflects these processes and therefore has untapped potential as an indicator of soil and ecosystem health. Under forest change, the FF might lose its functionality, with negative impacts on nutrient provision, water storage, and carbon sequestration. Consequences for forest growth could be strong and even detrimental. Hence, improved knowledge of FF characteristics and their linkages to mineral soils and aboveground ecosystem compartments is crucial for assessing forest resilience to progressing environmental changes.

Think pink 2.0 - Description of Roseobacter cerffii sp. nov., isolated from the chromerid alga Vitrella brassicaformis, and reclassification of Sulfitobacter sabulilitoris as Billmartinia sabulilitoris, gen. nov., comb. nov. - Jörn Petersen; Victoria Ringel; Orsola Päuker; Anja Frühling; Manfred Rohde; Michael Jarek; Cathrin Spröer; Boyke Bunk; Katharina Huber-Fischer; Silke Pradella; Heike M. Freese; Julia Koblitz; et al. (Systematic and Applied Microbiology, 2026)

Mirtazapine is a functional antagonist at cardiac human H1-histamine receptors - Thanh Hoai Pham; Jonas M. A. Schlicht; Britt Hofmann; Uwe Kirchhefer; Joachim Neumann; Ulrich Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Mirtazapine is an atypical tetracyclic antidepressant drug that binds to several monoamine neurotransmitter receptors. For instance, mirtazapine binds to H 1 -histamine receptors in vitro and in the brain of patients in vivo. Here, we hypothesize that mirtazapine is an antagonist at human cardiac H 1 -histamine receptors. To test this hypothesis, we measured force of contraction in isolated electrically stimulated (1 Hz) left atrial preparations (LA) and spontaneously beating right atrial preparations (RA) from adult transgenic mice with cardiomyocyte-specific overexpression of the human H 1 -histamine receptor (H 1 -TG). These findings were compared with those in wild-type littermate mice (WT). Finally, we measured the force of contraction in isolated electrically stimulated right atrial muscle strips (HAP) gotten from adult patients who were undergoing bypass surgery. Mirtazapine concentration- and time-dependently decreased H 1 -histamine receptor-stimulated force of contraction in LA and RA from H 1 -TG. Importantly, mirtazapine (starting at 100 nM) concentration- and time-dependently decreased H 1 -histamine receptor-stimulated force of contraction in HAP. We thus conclude that mirtazapine can antagonize human cardiac H 1 -histamine receptors at therapeutic drug concentrations, and thus, mirtazapine may have cardiac untoward effects in psychiatric patients.

Association between cardiovascular-kidney-metabolic syndrome and risks of 14 age-related health outcomes in primary prevention older population - Zhen Zhou; Kevan R. Polkinghorne; Andrew M. Tonkin; Robyn L. Woods; Anping Cai; Sophia Zoungas; Michelle A. Fravel; Michael E. Ernst; Chao Zhu; Mark Nelson; Johannes T. Neumann; Kerry M. Sheets; et al. (GeroScience, 2026)

Drivers of Viral Prevalence in Landscape‐Scale Pollinator Networks Across Europe: Honey Bee Viral Density, Niche Overlap With This Reservoir Host and Network Architecture - Willem Proesmans; Cedric Alaux; Matthias Albrecht; Karima Bassit; Nathan Cyrille; Anne Dalmon; Virginie Diévart; Christophe Dominik; Emeline Felten; Anna Gajda; Jonna M. Heuschele; Emilien Laurent; et al. (Ecology Letters, 2026)
Viral transfer from managed pollinators potentially threatens wild pollinators and may be exacerbated by land‐use changes. Our causal models and plant‐pollinator network data from 48 European urban and agricultural landscapes revealed the ecological mechanisms underpinning viral transmission. Host identity, network architecture and land‐use modulated viral dynamics (black queen cell virus, BQCV; deformed wing virus, DWV‐A and DWV‐B). Viral prevalence in wild pollinators was driven by viral density in the reservoir host: honey bees, and secondarily by trophic niche overlap with these managed pollinators. Modular networks limited BQCV prevalence, which was driven by reduced honey bee niche overlap, suggesting minimal onward transmission among wild pollinators. Landscapes supporting greater wild pollinator abundance diluted DWV‐B transmission; in urban landscapes managed honey bees and wild pollinators experienced higher and lower BQCV prevalence, respectively. Disease in managed bee colonies and land‐use changes that concentrate pollinator foraging interactions present potential viral risks to wild pollinator health.

Challenges in measuring the size and velocity of large raindrops: a comparison of selected methods - M. Beczek; M. Neumann; R. Mazur; D. Zumr; T. Dostal; A. Bieganowski (Journal of Hydrology, 2025)

Terrigenous inputs link nutrient dynamics to microbial communities in a tropical lagoon - Christian John; Nyssa J. Silbiger; Thomas C. Adam; Danielle M. Barnas; Kalia S. Bistolas; Robert C. Carpenter; Noe Castañeda; Megan J. Donahue; Mary K. Donovan; Lauren N. Enright; Hannah E. Epstein; Jordan P. Gallagher; et al. (Limnology and Oceanography, 2025)
Nutrient availability drives community structure and ecosystem processes, especially in tropical lagoons that are typically oligotrophic but often receive allochthonous inputs from land. Terrestrially derived nutrients are introduced to tropical lagoons by surface runoff and submarine groundwater discharge, which are influenced by seasonal precipitation. However, terrigenous inputs presumably diminish along the onshore–offshore gradients within lagoons. We characterized nutrient availability in the lagoons of a tropical high island, Moorea, French Polynesia, using spatially distributed measurements of nitrogen content in the tissues of a widespread macroalga during the rainy season over 4 yr. We used synoptic water column sampling to identify associations among macroalgal nutrient content and the composition of inorganic macronutrients, dissolved organic matter, and microbial communities. We paired these data with quantifications of land use in nearby watersheds to uncover links between terrestrial factors, aquatic chemistry, and microbial communities. Algal N content was highest near shore and near large, human‐impacted watersheds, and lower at offshore sites. Sites with high algal N had water columns with high nitrite + nitrate, silicate, and increased humic organic matter (based on a fluorescence Humification Index), especially following rain. Microbial communities were differentiated among nearshore habitats and covaried with algal N and water chemistry, supporting the hypothesis that terrigenous nutrient enrichment shapes microbial dynamics in otherwise oligotrophic tropical lagoons. This study reveals that land–sea connections create nutrient subsidies that are important for lagoon biogeochemistry and microbiology, indicating that future changes in land use or precipitation will modify ecosystem processes in tropical lagoons.

Toltrazuril sulfone (Ponazuril) residue depletion in pig tissues and estimated withdrawal intervals - Laura M. Neumann; Farha Sheela; Hiroko Enomoto; Jeremy Pittman; Ronald E. Baynes (Regulatory Toxicology and Pharmacology, 2025)

Machine learning model of submarine heat flow in the thermally unexplored northern Gulf of California Rift System - Luis Angel Vega-Ramírez; Juan Contreras; Karina Fuentes-Bustillos; Florian Neumann; Raquel Negrete-Aranda; Ronald M. Spelz; Ismael Yarbuh; Arturo Martín-Barajas; Mario González-Escobar (Geothermics, 2025)

Evidence of piscivorous diet in an enantiornithine bird from the Lower Cretaceous of Brazil - Fernando Luiz Kilesse Salgado; Luis M. Chiappe; Reiner Neumann; Ismar de Souza Carvalho (Cretaceous Research, 2025)

Elevated alpha-1 antitrypsin and C-reactive protein: association on all-cause and cause-specific mortality in older adults - Cammie Tran; Hans G. Schneider; Que T. Lam; Johannes T. Neumann; Flavia Cicuttini; Chenglong Yu; Zhen Zhou; Mark R. Nelson; Andrew M. Tonkin; Daniel Clayton-Chubb; Sultana Monira Hussain; Peter D. Fransquet; et al. (GeroScience, 2025)

Cretaceous–Paleogene palynodebris from two offshore cores in Cape Basin, South Atlantic Ocean and their paleoenvironmental implications - A. Sandersen; L. Scott; F.H. Neumann; E.W. Bergh; M. Bachari (Palaeoworld, 2025)

P24-23 Key Agronomic and Safety Characteristics (Key ASCs) and why they matter to improve safety and reduce reliance on animal testing for agricultural solutions - M. Corvaro; M. Battalora; L. Bertomeu; S. Ellis; I. Fegert; J.-C. Garcin; S. Kan-King-Yu; T. Mehta; S. Nadzialek; B. Neumann; P. Rawlinson; U. Rooni; et al. (Toxicology Letters, 2025)

Clozapine is a functional antagonist at cardiac human H2-histamine receptors - Jonas M. A. Schlicht; Undine Ahlrep; Britt Hofmann; Uwe Kirchhefer; Joachim Neumann; Ulrich Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Clozapine is an atypical antipsychotic (neuroleptic) drug. Clozapine binds to H 2 -histamine receptors in vitro. We wanted to test the hypothesis that clozapine might be a functional antagonist at human cardiac H 2 -histamine receptors. To that end, we studied isolated electrically stimulated left atrial preparations and spontaneously beating right atrial preparations from transgenic mice with cardiomyocyte-specific overexpression of the human H 2 -histamine receptor (H 2 -TG). For comparison, we used wild-type littermate mice (WT). Finally, we measured isometric force of contraction in isolated electrically stimulated muscle strips from the human right atrium (HAP) obtained from patients during bypass surgery. After pre-stimulation with histamine, clozapine (up to 10 µM) concentration and time dependently decreased beating rate in right atrial preparations from H 2 -TG. Clozapine concentration dependently 1, 3, and 10 µM decreased histamine-stimulated force of contraction in HAP. Clozapine (10 µM) decreased also the isoprenaline-stimulated force of contraction in HAP. In summary, clozapine can antagonize the function of H 2 -histamine and β-receptors in the human heart.

Identifying strategies to manage boreal forests: simulating moose and timber management scenarios at a landscape scale in the face of changing environmental conditions - Nathan R. De Jager; Wiebke Neumann; Miguel M. Girona; Joakim Hjältén; Anouschka R. Hof (European Journal of Forest Research, 2025)
There are ongoing debates among different stakeholders about which forest and ungulate management strategies will sustain high levels of timber and animal harvest and maintain important ecosystem functions under climate change. Ungulate-forest interactions are complex, including periods where forest regeneration is sensitive to browsing pressure, making it difficult to predict the consequences of a given strategy over time. To aid decision-making, we simulated the impacts of moose browsing on forest succession under 18 different combinations of moose ( Alces alces ) harvest rate levels and forest management scenarios in a boreal forest landscape in southern Sweden given projected changes in forest growth due to climate change. We found that the current management practices are important for sustaining a moose-forest system. Increasing moose harvest rates led to slightly smaller moose populations, larger estimates of landscape carrying capacity, and less biomass removal of Scots pine ( Pinus sylvestris ), a commercially valuable species. However, minor changes in the moose harvest were hardly affecting timber production. Increasing the timber harvest rotation time led to the highest estimates of Scots pine biomass, while thinning younger cohorts lead to the highest estimates of Norway spruce ( Picea abies ) biomass. These changes came without much effect to moose population dynamics. However, the increased broadleaf production scenario had a very large positive effect on total aboveground live biomass of deciduous species and on landscape carrying capacity and moose density. This scenario subsequently resulted in the greatest estimates of biomass removal of Scots pine, highlighting the tradeoffs associated with increased moose production.

Collective behavior diverges independently of the benthic-limnetic axis in stickleback - Kevin M. Neumann; Lucas Eckert; Damaris Miranda; Andrew Kemp; Alison M. Bell (Behavioral Ecology and Sociobiology, 2025)
Comparing populations across replicate environments or habitat types can help us understand the role of ecology in evolutionary processes. If similar phenotypes are favored in similar environments, parallel evolution may occur. Collective behavior, including collective movement and social networks, can play a key role in the adaptation by animals to different environments. However, studies exploring the parallelism of collective behavior are limited, with research traditionally focusing on morphological traits. Here, we asked if collective behavior varies consistently across replicate populations of benthic and limnetic three-spined stickleback ( Gasterosteus aculeatus ). There were repeatable, population-level differences in collective behavior in a common garden experiment, with some populations forming groups that were more cohesive and with higher strength and clustering coefficients. However, these differences were not predicted by ecotype (benthic vs. limnetic). Latency to emerge and morphology did consistently differ between ecotypes, and there were no correlations between these traits and collective behavior. Together, these results suggest that collective behavior diverges, but not in a way that is associated with variation along the benthic-limnetic axis. By examining multiple traits, we show how phenotypic evolution can be occurring in parallel and non-parallel ways at the same time. This study further highlights that the classification of habitat types may only be relevant for certain traits, with collective behavior potentially changing in a more nuanced manner.

Prevalence of aeroallergen sensitization in a polluted and industrialized area: a pilot study in South Africa’s Vaal Triangle - Dorra Gharbi; Frank Harald Neumann; Jurgens Staats; Marinda McDonald; Jo-hanné Linde; Tshiamo Mmatladi; Keneilwe Podile; Stuart Piketh; Roelof Burger; Rebecca M. Garland; Petra Bester; Pedro Humberto Lebre; et al. (Environmental Monitoring and Assessment, 2025)
This pioneering study evaluates the prevalence of aeroallergens reactivity among atopic populations living in the Vaal Triangle Airshed Priority Area (VTAPA), South Africa. A total of 138 volunteers (51 males and 87 females), of African, colored, white, and Asian ethnicity, and with a mean (range) age of 22 (18–56) years were participating in the study. The study was conducted on the North-West University (NWU) campus in Vanderbijlpark/VTAPA. The International Study of Asthma and Allergies in Childhood questionnaire was utilized for pre-screening to identify individuals with probable allergic dispositions. Subsequently, skin prick testing was conducted using commercial aeroallergen extracts for all confirmed participants with allergy symptoms. One hundred six participants were clinically diagnosed with pollen and fungal spore allergies. The highest allergy prevalence was attributed to Cynodon dactylon ((L.) Pers) (Bermuda grass) (41.5%), followed by Lolium perenne (L.) (ryegrass), grass mix, and Zea mays (L.) (maize) (31.1%), respectively. Moreover, among the tree allergens, Olea (L.) (olive tree) was the most prevalent allergen (20; 18.8%), followed by Platanus (L.) (plane tree) (18; 16.9%). Among the weeds, 16 (15.1%) participants were allergic to the weed mix ( Artemisia ( L. ) (wormwood), Chenopodium (Link) (goosefoot), Salsola (L.) (saltwort), Plantago (L.) (plantain), and 11 (10.3%) to Ambrosia (L.) (ragweed)). Regarding the fungal spores, Alternaria (Fr.) (9; 8.5%) followed by Cladosporium (Link) (5; 4.7%) had the highest skin sensitivity. In this pilot study, our findings provide insights into the prevalence of allergic responses in the study population—underlining the strong impact of allergens of exotic plants—and contribute to the existing aerobiological data in South Africa.

Contractile effects of stimulation of D1-dopamine receptors in the isolated human atrium - U. Gergs; T. H. Pham; L. M. Rayo Abella; C. Hesse; P. Grundig; S. Dhein; B. Hofmann; J. Neumann (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Dopamine receptors have been claimed not to directly increase contractility in the human heart. Therefore, we performed contraction experiments in isolated electrically driven human atrial preparations (HAP). For comparison, we performed contraction experiments with left atrial preparations of transgenic mice which harbor a cardiac overexpression of human D 1 -dopamine receptors (D 1 -TG). In D 1 -TG, first we noted that dopamine (10 nM–10 µM cumulatively applied) in the presence of propranolol exerted a concentration- and time-dependent positive inotropic effect in D 1 -TG. In a similar fashion, dopamine increased force of contraction in the presence of 0.4 µM propranolol in HAP and these effects were amplified by pre-treatment with inhibitor of phosphodiesterase III (1 µM) cilostamide. Moreover, contractile effects of dopamine in the presence of propranolol 0.4 µM in HAP were antagonized by odapipam, haloperidol, or raclopride. Ten micromolars of fenoldopam in the presence of cilostamide increased force of contraction in HAP and this effect was antagonized by SCH 23390. We conclude that stimulation of human D 1 -dopamine receptors can increase force of contraction in the HAP.

Transpiration and water use strategies of three economic tree species in a semi-arid afforestation region - Wenjie Wu; Yue Li; Kiril Manevski; Mathias Neumann Andersen; Bingcheng Si; Yongcai Lou; Hao Feng; Kadambot H. M. Siddique (European Journal of Forest Research, 2025)

Phylogenetic characterization of Bifidobacterium kimbladii sp. nov., a novel species from the honey stomach of the honeybee Apis mellifera - M. Modesto; D. Scarafile; A. Vásquez; R. Pukall; M. Neumann-Schaal; S. Pascarelli; B. Sgorbati; M. Ancora; C. Cammà; P. Mattarelli; T.C. Olofsson (Systematic and Applied Microbiology, 2025)

Trace element partitioning between natural barite and deep anoxic groundwaters: Implications for radionuclide retention in host rocks of nuclear waste repositories - Ferdinand Kirchner; Martin Kutzschbach; Henrik Drake; Vanessa Fichtner; Piotr M. Kowalski; Stefan Rudin; Martin J. Whitehouse; Mikael Tillberg; Thomas Neumann (Applied Geochemistry, 2024)

Nitrogen isotope homogenization of dissolved ammonium with depth and 15N enrichment of ammonium during incorporation into expandable layer silicates in organic-rich marine sediment from Guaymas Basin, Gulf of California - Toshiro Yamanaka; Arisa Sakamoto; Kanon Kiyokawa; Jaeguk Jo; Yuji Onishi; Yoshihiro Kuwahara; Ji-Hoon Kim; Lucie C. Pastor; Andreas Teske; Daniel Lizarralde; Tobias W. Höfig; Ivano W. Aiello; et al. (Chemical Geology, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Mineralization kinetics of biosiliceous sediments in hot subseafloors - Ivano W. Aiello; Tobias W. Höfig; Armelle Riboulleau; Andreas P. Teske; Daniel Lizarralde; Jeanine L. Ash; Diana P. Bojanova; Martine D. Buatier; Virginia P. Edgcomb; Christophe Y. Galerne; Swanne Gontharet; Verena B. Heuer; et al. (Geochimica et Cosmochimica Acta, 2024)

Healthy environments for athleTes (HEAT): environmental conditions along a 90 km ultra-marathon event, South Africa - H. Havenga; D. Gharbi; N. Sewry; B. Language; F. H. Neumann; J. M. Finch; T. Hill; J. Boulter; E. Jordaan; S. J. Piketh; M. Schwellnus; R. P. Burger (International Journal of Biometeorology, 2024)
This paper provides an overview of the HEAT (Healthy Environments for AthleTes) project, which aims to understand the impact of environmental conditions on athlete health and performance during major sporting events such as long-distance running, cycling, and triathlons. In collaboration with the SAFER (Strategies to reduce Adverse medical events For the ExerciseR) initiative, the HEAT project carried out a field campaign at the 2022 Comrades Marathon in the KwaZulu-Natal province of South Africa. The measurement campaign deployed seven weather stations, seven PM 2.5 monitors and one spore trap along the 90 km route to capture spatially representative measurements of complex micro-climates, allergenic aerospora, and particulate matter exposure. The results indicate that runners were exposed to moderate risk heat stress conditions. Novel findings from this initial campaign shows elevated and potentially harmful PM 2.5 levels at spectator areas, possibly coinciding with small fire events around the race day festivities. Our findings show values PM 2.5 levels over the WHO 24-h guidelines at all stations, while 2000 µg/m 3 at two stations. However, the lack of an acute exposure standard means direct health impacts cannot be quantified in the context of a sport event. The HEAT project highlights important aspects of race day monitoring; regional scale climatology has an impact on the race day conditions, the microclimatic conditions (pollution and meteorology) are not necessarily captured by proximity instruments and direct environmental measurements are required to accurately capture conditions along the route.

Overlooked and misunderstood: how urban community gardeners perceive social wasps and their ecosystem functions - Julia M. Schmack; Monika Egerer; Susan Karlebowski; Astrid E. Neumann; Ulrike Sturm (Journal of Insect Conservation, 2024)
Despite their importance for agricultural food production, many insects receive little to no positive attention. While bees have become the focus of insect conservation in agricultural landscapes, social wasps still rank among the most disliked animals and their ecological role and the ecosystem services they provide through e.g. pollination and pest control is subsequently understudied. We conducted a survey on the perceptions of social wasps and their ecosystem functions in urban community gardens in Berlin and Munich, Germany. We found that gardeners rated wasps as least beneficial for urban gardens among other insect taxa, and that predation was perceived as a negative function in insects and spiders. Respondent´s emotions were predominantly positive towards bees and negative towards wasps. Trivia questions about wasps revealed that knowledge of wasp ecology was positively associated with respondents´ willingness to share gardens with wasps. Implications for insect conservation: Our results show that urban gardeners´ negative perceptions of social wasps are likely driven by both a lack of knowledge about their ecological functions and a profusion of negative emotions towards wasps. Public outreach and education on the ecological importance of social wasps and other uncharismatic taxa as well as positive encounters with these specieshave the potential to improve their public image and thereby support the conservation of wasps and other insects.

OR-1896 increases force of contraction in the isolated human atrium - Lina M. Rayo-Abella; Peter Grundig; Max N. Bernhardt; Britt Hofmann; Joachim Neumann; Ulrich Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
OR-1896 ((R)-N-(4-(4-methyl-6-oxo-1,4,5,6-tetrahydropyridazin-3-yl)phenyl)acetamide) is the main active metabolite of levosimendan. However, nobody has reported a positive inotropic effect of OR-1896 in isolated human cardiac preparations. The mechanism of action of OR-1896 remains controversial. Hence, we wanted to know whether OR-1896 exerts a positive inotropic effect in humans and what might be the underlying mechanism. Therefore, we measured the contractile effects of OR-1896 (0.01–10 µM cumulatively applied) in isolated electrically stimulated (1 Hz) human right atrial preparations (HAP) obtained during cardiac surgery. OR-1896, given alone, exerted time- and concentration-dependent positive inotropic effects; 1-µM OR-1896 increased force by 72 ± 14.7% ( p < 0.05, n = 6) and shortened the time of relaxation by 10.6 ± 3.6% ( p < 0.05, n = 11) in HAP started at 0.1 µM, plateaued at 1-µM OR-1896, and was antagonized by 1-µM propranolol. The maximum positive inotropic effect of OR-1896 in human right atrial preparations was less than that of 10-µM isoprenaline. EMD 57033 (10 µM), a calcium sensitizer, enhanced the force of contraction further in the additional presence of 1-µM OR-1896 by 109 ± 19% ( p < 0.05, n = 4). Cilostamide (10 µM), an inhibitor of phosphodiesterase III given before OR-1896 (1 µM), blocked the positive inotropic effect of OR-1896 in HAP. Our data suggest that OR-1896 is, indeed, a positive inotropic agent in the human heart. OR-1896 acts as a PDE III inhibitor. OR-1896 is unlikely to act as a calcium sensitizer in the human heart.

Modern pollen- and phytolith-vegetation relationships at a wetland in northeastern South Africa - J.O. Olatoyan; F.H. Neumann; E.A. Orijemie; C. Sievers; M. Evans; T. Hattingh; M.H. Schoeman (South African Journal of Botany, 2023)

Proline and Silver Nitrate Promotes Multiple Shoot Induction from Mature Embryo and Shoot Tip Explants of Sorghum - B. D. Pawar; N. R. Markad; R. S. Wagh; M. Neumann; A. A. Kale; V. P. Chimote (Sugar Tech, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Sex-dependent associations of plasma high-density lipoprotein cholesterol and mortality risk in healthy older men and women: two prospective cohort studies - Sultana Monira Hussain; Andrew M Tonkin; Gerald F Watts; Paul Lacaze; Chenglong Yu; Lawrence J Beilin; Zhen Zhou; Anne B Newman; Johannes T Neumann; Cammie Tran; John J McNeil (GeroScience, 2023)
The relationship between high plasma high-density lipoprotein cholesterol (HDL-C) and cause and mortality are not well established in healthy older people. This study examined the associations between HDL-C levels and mortality in initially healthy older men and women. This analysis included participants from the Aspirin in Reducing Events in the Elderly (ASPREE; n =18,668) trial and a matched cohort from the UK Biobank (UKB; n =62,849 ≥65 years). Cox regression was used to examine hazard ratios between HDL-C categories <1.03 mmol/L, 1.03–1.55 mmol/L (referent category), 1.55–2.07 mmol/L, and >2.07 mmol/L and all-cause, cancer, cardiovascular disease (CVD), and “non-cancer non-CVD” mortality. Genetic contributions were assessed using a polygenic score for HDL-C. Among ASPREE participants (aged 75±5 years), 1836 deaths occurred over a mean follow-up of 6.3±1.8 years. In men, the highest category of HDL-C levels was associated with increased risk of all-cause (HR 1.60, 95% CI 1.26–2.03), cancer (HR 1.37, 95% CI 0.96–2.00), and “non-cancer non-CVD” mortality (HR 2.35, 95% CI 1.41–3.42) but not CVD mortality (HR 1.08, 95% CI 0.60–1.94). The associations were replicated among UKB participants (aged 66.9±1.5 years), including 8739 deaths over a mean follow-up of 12.7±0.8 years. There was a non-linear association between HDL-C levels and all-cause and cause-specific mortality. The association between HDL-C levels and mortality was unrelated to variations in the HDL-C polygenic score. No significant association was found between HDL-C levels and mortality in women. Higher HDL-C levels are associated with increased risk from cancer and “non-cancer non-CVD” mortality in healthy older men but no such relationship was observed in women.

Melissopalynological investigations of seasonal honey samples from the Greater Kruger National Park, Savanna biome of South Africa - Nikiwe Ndlovu; Frank H. Neumann; Michelle D. Henley; Robin M. Cook; Chevonne Reynolds (Palynology, 2023)

Thermal and behavioural responses of moose to chemical immobilisation from a helicopter - Anne Randi Græsli; Alexandra Thiel; Larissa T. Beumer; Boris Fuchs; Fredrik Stenbacka; Wiebke Neumann; Navinder J. Singh; Göran Ericsson; Jon M. Arnemo; Alina L. Evans (European Journal of Wildlife Research, 2023)
Instrumentation and sample collection for wildlife research and management may require chemical immobilisation of animals, which may entail physiological and behavioural effects on them. It is therefore important to evaluate the immobilisation protocols to reduce the risk of mortality and morbidity of the handled animals and their populations. Using a multi-sensor approach, we assessed the short-term (< 10 days) thermal and behavioural responses of 10 adult female moose ( Alces alces ) equipped with ruminal temperature loggers and GPS collars with accelerometers to helicopter-based chemical immobilisations. We investigated the body temperature ( T b ), movement rates, and resting time before, during, and after recapture. Chemical immobilisations on average increased maximum T b by 0.71 °C during the capture day, and imposed longer travel distances during the capture day and the two following days (3.8 and 1.8 km, respectively), compared to a 10-day reference period before the immobilisation. The probability of resting was 5–6% lower on the capture day and the two following days compared to the reference period, and females with offspring had a higher probability of resting than females without. Maximum T b , movement rate, and resting time returned to pre-capture levels on an individual level 2 h, 3 days, and 3 days after the immobilisation, respectively. Chemical immobilisation of moose from a helicopter increases the energy expenditure deduced through movement and T b rise lasting for hours to days. Ecological and physiological studies aimed at inferring general patterns may encounter bias if including sensor and tracking data from tagged animals without accounting for potential post-capture effects.

Carbohydrates in Kangaroo grass (Themeda triandra Forssk.) grain and perspectives on its food potential - James M. Cowley; Aaron L. Phillips; Shi Fang Khor; Tycho Neumann; Wai Li Lim; Rachel A. Burton (Journal of Cereal Science, 2023)

There is a trade-off between forest productivity and animal biodiversity in Europe - C. N. Khamila; T. A. Groen; A. G. Toxopeus; L. Santini; M. Neumann; C. Van Swaay; H. Sierdsema (Biodiversity and Conservation, 2023)
While forest productivity and biodiversity are expected to be correlated, prioritizing either forest productivity or biodiversity can result in different management. Spatial quantification of the congruence between areas suitable for either one can inform planning. Here we quantify the relationship between net primary productivity of European forests and biodiversity of mammals, birds, reptiles, amphibians, and butterflies both separately and in combination, and map their spatial congruence. We used richness maps obtained by stacking species distribution models for these animal species, and average net primary production from 2000 to 2012 using moderate resolution imaging spectroradiometer (MODIS) data. We tested how biodiversity and primary productivity are correlated and quantified the spatial congruence of these two sources. We show the areas where high or low productivity co-occur with high or low biodiversity using a quantile-based overlay analysis. Productivity was positively correlated to overall biodiversity and mammal, herptile and butterfly biodiversity, but biodiversity of birds showed a weak negative correlation. There were no significant differences in the strength of relationship across species groups, while herptiles had stronger relationships with productivity compared to other groups. Overlap analysis revealed significant spatial overlap between productivity and biodiversity in all species groups, except for birds. High value areas for both productivity and biodiversity in all species groups, except birds, co-occurred in the Mediterranean and temperate regions. The areas with high biodiversity of birds are mainly found in the boreal areas of Europe, while for all other species groups these areas are mostly located on the Iberian Peninsula and the Balkan ranges. Based on the presented maps, areas where regulating wood production activities to conserve species can be identified. But the maps also help to identify areas where either biodiversity or productivity is high and focusing on just one aspect is more straightforward.

Monitoring and evaluation of maritime spatial planning – A review of accumulated practices and guidance for future action - S.W.K. van den Burg; M. Skirtun; O. van der Valk; W. Rossi Cervi; T. Selnes; T. Neumann; J. Steinmann; G. Arora; P. Roebeling (Marine Policy, 2023)

Zooplankton exposure to microplastic contamination in a estuarine plume-influenced region, in Northeast Brazil - C.D.M. Lima; M. Melo Júnior; S.H.L. Schwamborn; F. Kessler; L.A. Oliveira; B.P. Ferreira; G. Mugrabe; J. Frias; S. Neumann-Leitão (Environmental Pollution, 2023)

The interplay of temperature and algal enrichment intensifies bioturbation of the intertidal amphipod Corophium volutator - Eilish M. Farrell; Jan Beermann; Andreas Neumann; Alexa Wrede (Journal of Experimental Marine Biology and Ecology, 2023)

Al-Mg and U-Pb chronological records of Erg Chech 002 ungrouped achondrite meteorite - Philip M. Reger; Yvonne Roebbert; Wladimir Neumann; Abdelmouhcine Gannoun; Marcel Regelous; Winfried H. Schwarz; Thomas Ludwig; Mario Trieloff; Stefan Weyer; Audrey Bouvier (Geochimica et Cosmochimica Acta, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Underground salt and potash workers exposed to nitrogen oxides and diesel exhaust: assessment of specific effect biomarkers - Lisa Gamrad-Streubel; Lisa-Marie Haase; Katharina K. Rudolph; Katrin Rühle; Annette M. Bachand; Lori Crawford; Kenneth A. Mundt; Jürgen Bünger; Dirk Pallapies; Dirk Taeger; Swaantje Casjens; Anja Molkenthin; et al. (International Archives of Occupational and Environmental Health, 2022)
Purpose Occupational exposure limits (OEL) for nitrogen oxides (NO, NO 2 ) and diesel exhaust (EC-DPM) were reassessed by the German authorities in 2016/2017. We performed a clinical cross-sectional study among salt and potash underground workers exposed to these substances at relatively high levels to examine possible indicators of acute effects on workers’ health. Methods We measured post- versus pre-shift differences in cardiovascular, inflammatory, immune, and respiratory effect biomarkers and assessed their associations with personal exposures measured during the same shift. We also compared post- versus pre-shift differences in biomarker levels between exposure groups defined based on work site and job type. Results None of the above-ground workers exceeded the OEL for NO 2 and only 5% exceeded the OEL for EC-DPM exposure. Among underground workers, 33% of miners and 7% underground maintenance workers exceeded the OEL for NO 2 ; the OEL for EC-DPM was exceeded by 56% of miners and 17% of maintenance workers. Some effect biomarkers (thrombocytes, neutrophils, MPO, TNF-α, IgE, FeNO) showed statistically significant differences between pre- versus post-shift measurements; however, there were no consistent associations between pre- and post-shift differences and exposure group or personal exposure measurements during the shift. Conclusions We did not find evidence of associations between workplace exposure to NO, NO 2 or EC-DPM and clinically relevant indicators of acute cardiovascular, inflammatory and immune, or respiratory effects among salt and potash underground workers in Germany.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

New phylogenetic insights into the African catfish families Mochokidae and Austroglanididae - Frederic D. B. Schedel; Albert Chakona; Brian L. Sidlauskas; Michael O. Popoola; Nadine Usimesa Wingi; Dirk Neumann; Emmanuel J. W. M. N. Vreven; Ulrich K. Schliewen (Journal of Fish Biology, 2022)
Several hundred catfish species (order: Siluriformes) belonging to 11 families inhabit Africa, of which at least six families are endemic to the continent. Although four of those families are well‐known to belong to the ‘Big‐Africa clade’, no previous study has addressed the phylogenetic placement of the endemic African catfish family Austroglanididae in a comprehensive framework with molecular data. Furthermore, interrelationships within the ‘Big‐Africa clade’, including the most diverse family Mochokidae, remain unclear. This study was therefore designed to help reconstruct inter‐ and intrarelationships of all currently valid mochokid genera, to infer their position within the ‘Big Africa clade’ and to establish a first molecular phylogenetic hypothesis of the relationships of the enigmatic Austroglanididae within the Siluriformes. We assembled a comprehensive mitogenomic dataset comprising all protein coding genes and representing almost all recognized catfish families ( N = 33 of 39) with carefully selected species ( N = 239). We recovered the monophyly of the previously identified multifamily clades ‘Big Asia’ and ‘Big Africa’ and determined Austroglanididae to be closely related to Pangasiidae, Ictaluroidea and Ariidae. Mochokidae was recovered as the sister group to a clade encompassing Auchenoglanididae, Claroteidae, Malapteruridae and the African Schilbeidae, albeit with low statistical support. The two mochokid subfamilies Mochokinae and Chiloglanidinae as well as the chiloglanid tribe Atopochilini were recovered as reciprocally monophyletic. The genus Acanthocleithron forms the sister group of all remaining Mochokinae, although with low support. The genus Atopodontus is the sister group of all remaining Atopochilini. In contrast to morphological reconstructions, the monophyly of the genus Chiloglanis was strongly supported in our analysis, with Chiloglanis macropterus nested within a Chiloglanis sublineage encompassing only other taxa from the Congo drainage. This is an important result because the phylogenetic relationships of C. macropterus have been controversial in the past, and because we and other researchers assumed that this species would be resolved as sister to most or all other members of Chiloglanis . The apparent paraphyly of Synodontis with respect to Microsynodontis provided an additional surprise, with Synodontis punu turning out to be the sister group of the latter genus.

Stepwise, earthquake-driven coastal subsidence in the Ganges–Brahmaputra Delta (Sundarbans) since the eighth century deduced from submerged in situ kiln and mangrove remnants - Till J. J. Hanebuth; Hermann R. Kudrass; Anja M. Zander; Humayun Syed Akhter; Gertrud Neumann-Denzau; Anwar Zahid (Natural Hazards, 2022)

Cardiovascular risk prediction in healthy older people - Johannes T. Neumann; Le T. P. Thao; Emily Callander; Enayet Chowdhury; Jeff D. Williamson; Mark R. Nelson; Geoffrey Donnan; Robyn L. Woods; Christopher M. Reid; Katrina K. Poppe; Rod Jackson; Andrew M. Tonkin; et al. (GeroScience, 2022)
Identification of individuals with increased risk of major adverse cardiovascular events (MACE) is important. However, algorithms specific to the elderly are lacking. Data were analysed from a randomised trial involving 18,548 participants ≥ 70 years old (mean age 75.4 years), without prior cardiovascular disease events, dementia or physical disability. MACE included coronary heart disease death, fatal or nonfatal ischaemic stroke or myocardial infarction. Potential predictors tested were based on prior evidence and using a machine-learning approach. Cox regression analyses were used to calculate 5-year predicted risk, and discrimination evaluated from receiver operating characteristic curves. Calibration was also assessed, and the findings internally validated using bootstrapping. External validation was performed in 25,138 healthy, elderly individuals in the primary care environment. During median follow-up of 4.7 years, 594 MACE occurred. Predictors in the final model included age, sex, smoking, systolic blood pressure, high-density lipoprotein cholesterol (HDL-c), non-HDL-c, serum creatinine, diabetes and intake of antihypertensive agents. With variable selection based on machine-learning, age, sex and creatinine were the most important predictors. The final model resulted in an area under the curve (AUC) of 68.1 (95% confidence intervals 65.9; 70.4). The model had an AUC of 67.5 in internal and 64.2 in external validation. The model rank-ordered risk well but underestimated absolute risk in the external validation cohort. A model predicting incident MACE in healthy, elderly individuals includes well-recognised, potentially reversible risk factors and notably, renal function. Calibration would be necessary when used in other populations.

Journal Club - Andreas Peschel; Andreas Diepold; Thilo M. Fuchs; Julia Ast; Marion Lemoine; Bernhard Schink; Kürşad Turgay; Bärbel Stecher; Kai Thormann; Remy Colin; Johannes Sander; Petra Neumann-Staubitz; et al. (BIOspektrum, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Correction to: Current evidence on the impact of medication optimization or pharmacological interventions on frailty or aspects of frailty: a systematic review of randomized controlled trials - Farhad Pazan; Mirko Petrovic; Antonio Cherubini; Graziano Onder; Alfonso J. Cruz-Jentoft; Michael Denkinger; Tischa J. M. van der Cammen; Jennifer M. Stevenson; Kinda Ibrahim; Chakravarthi Rajkumar; Marit Stordal Bakken; Jean-Pierre Baeyens; et al. (European Journal of Clinical Pharmacology, 2021)

Genome sequencing in families with congenital limb malformations - Jonas Elsner; Martin A. Mensah; Manuel Holtgrewe; Jakob Hertzberg; Stefania Bigoni; Andreas Busche; Marie Coutelier; Deepthi C. de Silva; Nursel Elçioglu; Isabel Filges; Erica Gerkes; Katta M. Girisha; et al. (Human Genetics, 2021)
The extensive clinical and genetic heterogeneity of congenital limb malformation calls for comprehensive genome-wide analysis of genetic variation. Genome sequencing (GS) has the potential to identify all genetic variants. Here we aim to determine the diagnostic potential of GS as a comprehensive one-test-for-all strategy in a cohort of undiagnosed patients with congenital limb malformations. We collected 69 cases (64 trios, 1 duo, 5 singletons) with congenital limb malformations with no molecular diagnosis after standard clinical genetic testing and performed genome sequencing. We also developed a framework to identify potential noncoding pathogenic variants. We identified likely pathogenic/disease-associated variants in 12 cases (17.4%) including four in known disease genes, and one repeat expansion in HOXD13 . In three unrelated cases with ectrodactyly, we identified likely pathogenic variants in UBA2 , establishing it as a novel disease gene. In addition, we found two complex structural variants (3%). We also identified likely causative variants in three novel high confidence candidate genes. We were not able to identify any noncoding variants. GS is a powerful strategy to identify all types of genomic variants associated with congenital limb malformation, including repeat expansions and complex structural variants missed by standard diagnostic approaches. In this cohort, no causative noncoding SNVs could be identified.

Geochemistry of deep Tunguska Basin sills, Siberian Traps: correlations and potential implications for the end-Permian environmental crisis - S. Callegaro; H. H. Svensen; E. R. Neumann; A. G. Polozov; D. A. Jerram; F. M. Deegan; S. Planke; O. V. Shiganova; N. A. Ivanova; N. V. Melnikov (Contributions to Mineralogy and Petrology, 2021)
A vast portion of the plumbing system of the Siberian Traps Large Igneous Province (STLIP) is emplaced in the Tunguska Basin, where borehole data reveal ubiquitous and abundant sills with great lateral extension. These intrusions intersect Cambrian–Ordovician evaporite, carbonate and siliciclastic series, and locally coal-bearing Permian host rocks, with a high potential for thermogenic gas generation. Here we present new geochemical data from 71 magmatic and 4 sedimentary rock samples from the Tunguska Basin center and periphery, recovered from 15 deep sills intercepted by boreholes. The studied samples are all low-Ti basalt and basaltic andesites, confirming absence of high-Ti and alkaline STLIP magmatism in the Tunguska Basin. The sills derive from picritic parental melts produced by extensive melting of a mantle source with recycled crustal components below a thinned lithosphere (50–60 km), within the spinel stability field. The mantle source was dominantly peridotitic, with enriched pyroxenitic domains formed by recycled lower crust, in agreement with previous models for the main tholeiitic STLIP phase. Limited amounts (up to 5%) of highly radiogenic granitoids or moderately radiogenic metapelites were assimilated in upper crustal magma reservoirs. After emplacement, sills intruded in Cambrian evaporites assimilated marlstones and interacted with the evaporitic host rocks, probably via fluids and brines. This is the first time that such process is described in subvolcanic rocks from all across the volcanic basin. The sills are correlated geochemically with the established chemostratigraphy for the on-craton STLIP lava piles and intrusions (Norilsk region). Sills correlated with the Morongovsky–Mokulaevsky Fm. and the Norilsk-type intrusions are the most voluminous, present all across the central Tunguska Basin, and bear the strongest evidence of interaction with evaporites. Massive discharge of thermogenic volatiles is suggested by explosive pipes and hydrothermal vent structures throughout the Tunguska Basin. We propose that this voluminous pulse of magmatism is a good candidate for the hitherto unidentified early intrusive phase of the STLIP, and may link the deep Tunguska basin sills to the end-Permian environmental crisis.

The place beyond the trees: renewed excavations of the Middle Stone Age deposits at Olieboomspoort in the Waterberg Mountains of the South African Savanna Biome - A. Val; P. de la Peña; M. Duval; S. Bansal; F. Colino; J. Culey; T. Hodgskiss; P. Morrissey; A. Murray; M. Murungi; F.H. Neumann; K. Shadrach; et al. (Archaeological and Anthropological Sciences, 2021)
Olieboomspoort is one of the few rock shelters in the vast interior of southern Africa documenting pulses of occupation from the Acheulean until the end of the Later Stone Age. Revil Mason excavated the site in 1954 and attributed the large Middle Stone Age (MSA) lithic assemblage to his middle phase of the so-called Pietersburg Industry. Recent work at the site has focused on the Holocene layers, but little is known about the earlier phases of shelter use. Here, we provide some background to the shelter, give a history of past research and present initial results following renewed fieldwork at the site. The MSA deposits contain abundant lithic artefacts and ochre, and we present an initial description of these cultural remains. Palynological analysis reveals limited potential for palaeoenvironmental reconstructions, but some faunal remains indicate open grasslands. We dated two equid teeth that provided highly consistent combined U-series-ESR estimates, resulting in a mean age of 150 ± 14 ka (1σ). Even when considering potential sources of uncertainty such as variations in water-intake, these fossils can securely be dated to Marine Isotopic Stage 6. Our reappraisal of site formation processes highlights the fact that the archaeological assemblage is strongly time-averaged. We discuss these different results in the context of a recently rekindled interest in the so-called Pietersburg Industry.

Current evidence on the impact of medication optimization or pharmacological interventions on frailty or aspects of frailty: a systematic review of randomized controlled trials - Farhad Pazan; Mirko Petrovic; Antonio Cherubini; Graziano Onder; Alfonso J. Cruz-Jentoft; Michael Denkinger; Tischa J. M. van der Cammen; Jennifer M. Stevenson; Kinda Ibrahim; Chakravarthi Rajkumar; Marit Stordal Bakken; Jean-Pierre Baeyens; et al. (European Journal of Clinical Pharmacology, 2021)
Background Frailty and adverse drug effects are linked in the fact that polypharmacy is correlated with the severity of frailty; however, a causal relation has not been proven in older people with clinically manifest frailty. Methods A literature search was performed in Medline to detect prospective randomized controlled trials (RCTs) testing the effects of pharmacological interventions or medication optimization in older frail adults on comprehensive frailty scores or partial aspects of frailty that were published from January 1998 to October 2019. Results Twenty-five studies were identified, 4 on comprehensive frailty scores and 21 on aspects of frailty. Two trials on comprehensive frailty scores showed positive results on frailty although the contribution of medication review in a multidimensional approach was unclear. In the studies on aspects related to frailty, ten individual drug interventions showed improvement in physical performance, muscle strength or body composition utilizing alfacalcidol, teriparatide, piroxicam, testosterone, recombinant human chorionic gonadotropin, or capromorelin. There were no studies examining negative effects of drugs on frailty. Conclusion So far, data on a causal relationship between drugs and frailty are inconclusive or related to single-drug interventions on partial aspects of frailty. There is a clear need for RCTs on this topic that should be based on a comprehensive, internationally consistent and thus reproducible concept of frailty assessment.

Correction to: Strength of correlation between wildlife collision data and hunting bags varies among ungulate species and with management scale - Wiebke Neumann; Fredrik Widemo; Navinder J. Singh; Andreas Seiler; Joris P. G. M. Cromsigt (European Journal of Wildlife Research, 2020)

Strength of correlation between wildlife collision data and hunting bags varies among ungulate species and with management scale - Wiebke Neumann; Fredrik Widemo; Navinder J. Singh; Andreas Seiler; Joris P. G. M. Cromsigt (European Journal of Wildlife Research, 2020)
Most European ungulate species are increasing in numbers and expanding their range. For the management and monitoring of these species, 64% of European countries rely on indirect proxies of abundance (e.g., hunting bag statistics). With increasing ungulate numbers, data on ungulate-vehicle collisions (UVC) may provide an important and inexpensive, complementary data source. Currently, it is unclear how bag statistics compare with UVC. A direct comparison of these two indices is important because both are used in ungulate management. We evaluated the relationship between UVC and ungulate hunting bags across bioclimatic, regional, and local scales, using five time lags (t −3 to t +1 ) for the five most common wild ungulate species in Sweden. For all species, hunting bags and UVC correlated positively, but correlation strength and time lags varied across scales and among species. The two indices correlated most strongly at the local management scale. Correlation between both indices was strong for the smaller deer species and wild boar, in particular, but much weaker for moose where we found the best fit using a 2-year time lag. For the other species, indices from the same year correlated best. We argue that the reason for moose data behaving differently is that, in Sweden, moose are formally managed using a 3-year time plan, while the other species are not. Accordingly, moose hunting bags are influenced more strongly by density-independent processes than bags of the other species. Consequently, the mismatch between the two indices may generate conflicting conclusions for management depending on the method applied.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Medical Toxicology Education and Global Health: It is Still a World of Limited Resources in Low- and Middle-Income Countries - Natalie R. Neumann; Trevonne M. Thompson (Journal of Medical Toxicology, 2020)

Comment on the letter of the Society of Vertebrate Paleontology (SVP) dated April 21, 2020 regarding “Fossils from conflict zones and reproducibility of fossil-based scientific data”: the importance of private collections - Carolin Haug; Jelle W. F. Reumer; Joachim T. Haug; Antonio Arillo; Denis Audo; Dany Azar; Viktor Baranov; Rolf Beutel; Sylvain Charbonnier; Rodney Feldmann; Christian Foth; René H. B. Fraaije; et al. (PalZ, 2020)

Comment on the letter of the Society of Vertebrate Paleontology (SVP) dated April 21, 2020 regarding “Fossils from conflict zones and reproducibility of fossil-based scientific data”: Myanmar amber - Joachim T. Haug; Dany Azar; Andrew Ross; Jacek Szwedo; Bo Wang; Antonio Arillo; Viktor Baranov; Julia Bechteler; Rolf Beutel; Vladimir Blagoderov; Xavier Delclòs; Jason Dunlop; et al. (PalZ, 2020)

Medical Toxicology and COVID-19: Our Role in a Pandemic - Natalie R. Neumann; Peter R. Chai; David M. Wood; Howard A. Greller; Mark B. Mycyk (Journal of Medical Toxicology, 2020)

Nitrogen isotope values of Pennisetum glaucum (pearl millet) grains: towards a reconstruction of past cultivation conditions in the Sahel, West Africa - Amy K. Styring; Amadou M. Diop; Amy Bogaard; Louis Champion; Dorian Q. Fuller; Nikolas Gestrich; Kevin C. Macdonald; Katharina Neumann (Vegetation History and Archaeobotany, 2019)

Quantification of PpIX-fluorescence of cerebral metastases: a pilot study - Johannes Knipps; Igor Fischer; Lisa M. Neumann; Marion Rapp; Maxine Dibué-Adjei; Christiane Freiin von Saß; Jan-Malte Placke; Hendrik-Jan Mijderwijk; Hans-Jakob Steiger; Michael Sabel; Jan-Frederick Cornelius; Marcel A. Kamp (Clinical & Experimental Metastasis, 2019)

Stochastic 3D Modeling of Three-Phase Microstructures for Predicting Transport Properties: A Case Study - M. Neumann; B. Abdallah; L. Holzer; F. Willot; V. Schmidt (Transport in Porous Media, 2019)

Contrasting arsenic cycling in strongly and weakly stratified contaminated lakes: Evidence for temperature control on sediment–water arsenic fluxes - P. M. Barrett; E. A. Hull; K. Burkart; O. Hargrave; J. McLean; V. F. Taylor; B. P. Jackson; J. E. Gawel; R. B. Neumann (Limnology and Oceanography, 2019)
Arsenic contamination of lakebed sediments is widespread due to a range of human activities, including herbicide application, waste disposal, mining, and smelter operations. The threat to aquatic ecosystems and human health is dependent on the degree of mobilization from sediments into overlying water columns and exposure of aquatic organisms. We undertook a mechanistic investigation of arsenic cycling in two impacted lakes within the Puget Sound region, a shallow weakly stratified lake and a deep seasonally stratified lake, with similar levels of lakebed arsenic contamination. We found that the processes that cycle arsenic between sediments and the water column differed greatly in shallow and deep lakes. In the shallow lake, seasonal temperature increases at the lakebed surface resulted in high porewater arsenic concentrations that drove larger diffusive fluxes of arsenic across the sediment–water interface compared to the deep, stratified lake where the lakebed remained ~10°C cooler. Plankton in the shallow lake accumulated up to an order of magnitude more arsenic than plankton in the deep lake due to elevated aqueous arsenic concentrations in oxygenated waters and low phosphate : arsenate ratios in the shallow lake. As a result, strong arsenic mobilization from sediments in the shallow lake was countered by large arsenic sedimentation rates out of the water column driven by plankton settling.

Limitations of Weight Velocity Analysis by Commercial Computer Program Growth Analyser Viewer Edition - Martin J. C. van Gemert; Cornelis M. A. Bruijninckx; Ton G. van Leeuwen; H. A. Martino Neumann; Pieter J. J. Sauer (Annals of Biomedical Engineering, 2019)

Effects of ketamine on brain function during response inhibition - M. Steffens; C. Neumann; A.-M. Kasparbauer; B. Becker; B. Weber; M. A. Mehta; R. Hurlemann; U. Ettinger (Psychopharmacology, 2018)

Extracellular Matrix Expression and Production in Fibroblast-Collagen Gels: Towards an In Vitro Model for Ligament Wound Healing - Stephanie M. Frahs; Julia Thom Oxford; Erica E. Neumann; Raquel J. Brown; Cynthia R. Keller-Peck; Xinzhu Pu; Trevor J. Lujan (Annals of Biomedical Engineering, 2018)

Evaluation of a reducible disulfide linker for siderophore-mediated delivery of antibiotics - Wilma Neumann; Elizabeth M. Nolan (JBIC Journal of Biological Inorganic Chemistry, 2018)

EFO-LCI: A New Life Cycle Inventory Database of Forestry Operations in Europe - Giuseppe Cardellini; Tatiana Valada; Claire Cornillier; Estelle Vial; Marian Dragoi; Venceslas Goudiaby; Volker Mues; Bruno Lasserre; Arkadiusz Gruchala; Per Kristian Rørstad; Mathias Neumann; Miroslav Svoboda; et al. (Environmental Management, 2018)

Tubulin alpha 8 is expressed in hepatic stellate cells and is induced in transformed hepatocytes - Lisa Rein-Fischboeck; Rebekka Pohl; Elisabeth M. Haberl; Sebastian Zimny; Maximilian Neumann; Kristina Eisinger; Thomas S. Weiss; Sabrina Krautbauer; Christa Buechler (Molecular and Cellular Biochemistry, 2017)

Developments in pre-treatment methods to improve anaerobic digestion of sewage sludge - P. Neumann; S. Pesante; M. Venegas; G. Vidal (Reviews in Environmental Science and Bio/Technology, 2016)

No spatial patterns for early nectar storage in honey bee colonies - M. Eyer; M. K. Greco; J. Lang; P. Neumann; V. Dietemann (Insectes Sociaux, 2016)

Digital and real-habitat modeling of Hipparchia statilinus based on hyper spectral remote sensing data - L. Luft; C. Neumann; S. Itzerott; A. Lausch; D. Doktor; M. Freude; N. Blaum; F. Jeltsch (International Journal of Environmental Science and Technology, 2016)

Offset between GPS collar-recorded temperature in moose and ambient weather station data - Göran Ericsson; Holger Dettki; Wiebke Neumann; Jon M. Arnemo; Navinder J. Singh (European Journal of Wildlife Research, 2015)

Effects, but no interactions, of ubiquitous pesticide and parasite stressors on honey bee ( A pis mellifera ) lifespan and behaviour in a colony environment - Gina Retschnig; Geoffrey R. Williams; Richard Odemer; Janina Boltin; Cornelia Di Poto; Marion M. Mehmann; Peter Retschnig; Pius Winiger; Peter Rosenkranz; Peter Neumann (Environmental Microbiology, 2015)
Summary Interactions between pesticides and parasites are believed to be responsible for increased mortality of honey bee ( A pis mellifera ) colonies in the northern hemisphere. Previous efforts have employed experimental approaches using small groups under laboratory conditions to investigate influence of these stressors on honey bee physiology and behaviour, although both the colony level and field conditions play a key role for eusocial honey bees. Here, we challenged honey bee workers under in vivo colony conditions with sublethal doses of the neonicotinoid thiacloprid, the miticide tau‐fluvalinate and the endoparasite N osema ceranae , to investigate potential effects on longevity and behaviour using observation hives. In contrast to previous laboratory studies, our results do not suggest interactions among stressors, but rather lone effects of pesticides and the parasite on mortality and behaviour, respectively. These effects appear to be weak due to different outcomes at the two study sites, thereby suggesting that the role of thiacloprid, tau‐fluvalinate and N . ceranae and interactions among them may have been overemphasized. In the future, investigations into the effects of honey bee stressors should prioritize the use of colonies maintained under a variety of environmental conditions in order to obtain more biologically relevant data.

Different utilization of alginate and other algal polysaccharides by marine A lteromonas macleodii ecotypes - Anna M. Neumann; John P. Balmonte; Martine Berger; Helge‐Ansgar Giebel; Carol Arnosti; Sonja Voget; Meinhard Simon; Thorsten Brinkhoff; Matthias Wietz (Environmental Microbiology, 2015)
Summary The marine bacterium A lteromonas macleodii is a copiotrophic r ‐strategist, but little is known about its potential to degrade polysaccharides. Here, we studied the degradation of alginate and other algal polysaccharides by A . macleodii strain 83‐1 in comparison to other A . macleodii strains. Cell densities of strain 83‐1 with alginate as sole carbon source were comparable to those with glucose, but the exponential phase was delayed. The genome of 83‐1 was found to harbour an alginolytic system comprising five alginate lyases, whose expression was induced by alginate. The alginolytic system contains additional CAZ ymes, including two TonB ‐dependent receptors, and is part of a 24 kb genomic island unique to the A . macleodii ‘ surface clade’ ecotype. In contrast, strains of the ‘deep clade’ ecotype contain only a single alginate lyase in a separate 7 kb island. This difference was reflected in an eightfold greater efficiency of surface clade strains to grow on alginate. Strain 83‐1 furthermore hydrolysed laminarin, pullulan and xylan, and corresponding polysaccharide utilization loci were detected in the genome. A lteromonas macleodii alginate lyases were predominantly detected in Atlantic Ocean metagenomes. The demonstrated hydrolytic capacities are likely of ecological relevance and represent another level of adaptation among A . macleodii ecotypes.

Benefits of greenhouse gas mitigation on the supply, management, and use of water resources in the United States - K. Strzepek; J. Neumann; J. Smith; J. Martinich; B. Boehlert; M. Hejazi; J. Henderson; C. Wobus; R. Jones; K. Calvin; D. Johnson; E. Monier; et al. (Climatic Change, 2015)

Human mesenchymal stem cells express a myofibroblastic phenotype in vitro: comparison to human cardiac myofibroblasts - Melanie A. Ngo; Alison Müller; Yun Li; Shannon Neumann; Ganghong Tian; Ian M. C. Dixon; Rakesh C. Arora; Darren H. Freed (Molecular and Cellular Biochemistry, 2014)

Improving cross-sectoral climate change adaptation for coastal settlements: insights from South East Queensland, Australia - S. Serrao-Neumann; F. Crick; B. Harman; M. Sano; O. Sahin; R. van Staden; G. Schuch; S. Baum; D. Low Choy (Regional Environmental Change, 2014)

Echoes from the Past: A Healthy Baltic Sea Requires More Effort - Aarno T. Kotilainen; Laura Arppe; Slawomir Dobosz; Eystein Jansen; Karoline Kabel; Juha Karhu; Mia M. Kotilainen; Antoon Kuijpers; Bryan C. Lougheed; H. E. Markus Meier; Matthias Moros; Thomas Neumann; et al. (Ambio, 2014)

The effect of partial outlet obstruction on calpain and phospholipase-2 activities: analyzed by severity and duration - Connor M. Callaghan; Arnold Johnson; Paul Neumann; Robert E. Leggett; Catherine Schuler; Robert M. Levin (Molecular and Cellular Biochemistry, 2013)

Microbial communities along biogeochemical gradients in a hydrocarbon‐contaminated aquifer - Karolin Tischer; Sabine Kleinsteuber; Kathleen M. Schleinitz; Ingo Fetzer; Oliver Spott; Florian Stange; Ute Lohse; Janett Franz; Franziska Neumann; Sarah Gerling; Christian Schmidt; Eyk Hasselwander; et al. (Environmental Microbiology, 2013)
Summary Micro‐organisms are known to degrade a wide range of toxic substances. How the environment shapes microbial communities in polluted ecosystems and thus influences degradation capabilities is not yet fully understood. In this study, we investigated microbial communities in a highly complex environment: the capillary fringe and subjacent sediments in a hydrocarbon‐contaminated aquifer. Sixty sediment sections were analysed using terminal restriction fragment length polymorphism ( T‐RFLP ) fingerprinting, cloning and sequencing of bacterial and archaeal 16 S rRNA genes, complemented by chemical analyses of petroleum hydrocarbons, methane, oxygen and alternative terminal electron acceptors. Multivariate statistics revealed concentrations of contaminants and the position of the water table as significant factors shaping the microbial community composition. Micro‐organisms with highest T‐RFLP abundances were related to sulphate reducers belonging to the genus D esulfosporosinus , fermenting bacteria of the genera S edimentibacter and S mithella , and aerobic hydrocarbon degraders of the genus A cidovorax . Furthermore, the acetoclastic methanogens M ethanosaeta , and hydrogenotrophic methanogens M ethanocella and M ethanoregula were detected. Whereas sulphate and sulphate reducers prevail at the contamination source, the detection of methane, fermenting bacteria and methanogenic archaea further downstream points towards syntrophic hydrocarbon degradation.

Depositional systems in the Mt Isa Inlier from 1800 Ma to 1640 Ma: Implications for Zn–Pb–Ag mineralisation - P. N. Southgate; N. L. NEUMANN; G. M. GIBSON (Australian Journal of Earth Sciences, 2013)

An association mapping analysis of dormancy and pre-harvest sprouting in wheat - M. A. Rehman Arif; K. Neumann; M. Nagel; B. Kobiljski; U. Lohwasser; A. Börner (Euphytica, 2012)

Performance of a novel microarray multiplex PCR for the detection of 23 respiratory pathogens (SYMP-ARI study) - S. Bierbaum; N. Königsfeld; N. Besazza; K. Blessing; G. Rücker; U. Kontny; R. Berner; M. Schumacher; J. Forster; V. Falcone; C. Sand; A. Essig; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Nephron sparing surgery in von Hippel-Lindau associated renal cell carcinoma; clinicopathological long-term follow-up - C. A. Jilg; Hartmut P. H. Neumann; S. Gläsker; O. Schäfer; C. Leiber; P. U. Ardelt; M. Schwardt; W. Schultze-Seemann (Familial Cancer, 2012)

Genetic studies of seed longevity in hexaploid wheat using segregation and association mapping approaches - M. A. Rehman Arif; M. Nagel; K. Neumann; B. Kobiljski; U. Lohwasser; A. Börner (Euphytica, 2012)

Strong decline of gene diversity in local populations of the highly endangered Common hamster (Cricetus cricetus) in the western part of its European range - M. J. J. La Haye; K. Neumann; H. P. Koelewijn (Conservation Genetics, 2012)

Orbit determination of the Lunar Reconnaissance Orbiter - Erwan Mazarico; D. D. Rowlands; G. A. Neumann; D. E. Smith; M. H. Torrence; F. G. Lemoine; M. T. Zuber (Journal of Geodesy, 2012)

Novel Types of Frontotemporal Lobar Degeneration: Beyond Tau and TDP-43 - Ian R. A. Mackenzie; Manuela Neumann; Nigel J. Cairns; David G. Munoz; Adrian M. Isaacs (Journal of Molecular Neuroscience, 2011)

Protein phosphatase 2A affects myofilament contractility in non-failing but not in failing human myocardium - Paul J. M. Wijnker; Peter Boknik; Ulrich Gergs; Frank U. Müller; Joachim Neumann; Cris dos Remedios; Wilhelm Schmitz; Jürgen R. Sindermann; Ger J. M. Stienen; Jolanda van der Velden; Uwe Kirchhefer (Journal of Muscle Research and Cell Motility, 2011)

Evaluation of LC-high-resolution FT-Orbitrap MS for the quantification of selected mycotoxins and the simultaneous screening of fungal metabolites in food - S.M. Lehner; N.K.N. Neumann; M. Sulyok; M. Lemmens; R. Krska; R. Schuhmacher (Food Additives & Contaminants: Part A, 2011)

Human antimicrobial proteins in ear wax - M. Schwaab; A. Gurr; A. Neumann; S. Dazert; A. Minovi (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Behavioral defense strategies of the stingless bee, Austroplebeia australis, against the small hive beetle, Aethina tumida - M. Halcroft; R. Spooner-Hart; P. Neumann (Insectes Sociaux, 2011)

Foraging behavior of golden hamsters (Mesocricetus auratus) in the wild - S. C. Larimer; P. Fritzsche; Z. Song; J. Johnston; K. Neumann; R. Gattermann; M. E. McPhee; R. E. Johnston (Journal of Ethology, 2011)

Demersal zooplankton communities from tropical habitats in the southwestern Atlantic - Pedro A. M. C. Melo; Tâmara A. Silva; Sigrid Neumann-Leitão; Ralf Schwamborn; Lucia M. O. Gusmão; Fernando Porto Neto (Marine Biology Research, 2010)

Rhizosphere humic acid interacts with root cell walls to reduce hydraulic conductivity and plant development - Sare Asli; Peter M. Neumann (Plant and Soil, 2010)

Classifying polarimetric SAR data by combining expectation methods with spatial context - A. Reigber; M. Jäger; M. Neumann; L. Ferro-Famil (International Journal of Remote Sensing, 2010)

New SHRIMP age constraints on the timing and duration of magmatism and sedimentation in the Mary Kathleen Fold Belt, Mt Isa Inlier, Australia - N. L. Neumann; G. M. Gibson; P. N. Southgate (Australian Journal of Earth Sciences, 2009)

New directions for improving the management of agricultural soils - Raphael Linker; Peter M. Neumann (Plant and Soil, 2008)

Composition and thermal structure of the lithosphere beneath the Ethiopian plateau: evidence from mantle xenoliths in basanites, Injibara, Lake Tana Province - S. Ferrando; M. L. Frezzotti; E.-R. Neumann; G. De Astis; A. Peccerillo; A. Dereje; Y. Gezahegn; A. Teklewold (Mineralogy and Petrology, 2008)

Pollution-Affected Fish Hepatic Transcriptome and Its Expression Patterns on Exposure to Cadmium - M. Auslander; Y. Yudkovski; V. Chalifa-Caspi; B. Herut; R. Ophir; R. Reinhardt; P. M. Neumann; M. Tom (Marine Biotechnology, 2008)

Return of twaite shad Alosa fallax (Lacépède, 1803) to the Southern Baltic Sea and the transitional area between the Baltic and North Seas - Ralf Thiel; Philip Riel; Renate Neumann; Helmut M. Winkler; Uwe Böttcher; Tomas Gröhsler (Hydrobiologia, 2008)

Bee-hawking by the wasp, Vespa velutina, on the honeybees Apis cerana and A. mellifera - K. Tan; S. E. Radloff; J. J. Li; H. R. Hepburn; M. X. Yang; L. J. Zhang; P. Neumann (The Science of Nature, 2007)

Mutations in autism susceptibility candidate 2 (AUTS2) in patients with mental retardation - Vera M. Kalscheuer; David FitzPatrick; Niels Tommerup; Merete Bugge; Erik Niebuhr; Luitgard M. Neumann; Andreas Tzschach; Sarah A. Shoichet; Corinna Menzel; Fikret Erdogan; Ger Arkesteijn; Hans-Hilger Ropers; et al. (Human Genetics, 2007)

Remote Non-invasive Stereoscopic Imaging of Blood Vessels: First In-vivo Results of a New Multispectral Contrast Enhancement Technology - F. P. Wieringa; F. Mastik; F. J. ten Cate; H. A. M. Neumann; A. F. W. van der Steen (Annals of Biomedical Engineering, 2006)

Social parasitism by honeybee workers (Apis mellifera capensis Esch.): evidence for pheromonal resistance to host queen’s signals - Vincent Dietemann; Jochen Pflugfelder; Stephan Härtel; Peter Neumann; Robin M. Crewe (Behavioral Ecology and Sociobiology, 2006)

Evidence for a new contiguous gene syndrome, the chromosome 16p13.3 deletion syndrome alias severe Rubinstein–Taybi syndrome - Oliver Bartsch; Sasan Rasi; Alicia Delicado; Sarah Dyack; Luitgard M. Neumann; Eva Seemanová; Marianne Volleth; Thomas Haaf; Vera M. Kalscheuer (Human Genetics, 2006)

Individual versus social pathway to honeybee worker reproduction (Apis mellifera): pollen or jelly as protein source for oogenesis? - M. O. Schäfer; V. Dietemann; C. W. W. Pirk; P. Neumann; R. M. Crewe; H. R. Hepburn; J. Tautz; K. Crailsheim (Journal of Comparative Physiology A, 2006)

Cells of Pseudomonas putida and Enterobacter sp. adapt to toxic organic compounds by increasing their size - Grit Neumann; Y. Veeranagouda; T. B. Karegoudar; zlem Sahin; Ines Musezahl; Nadja Kabelitz; Uwe Kappelmeyer; Hermann J. Heipieper (Extremophiles, 2005)

Salt (NaCl) tolerance in the Ni hyperaccumulator Alyssum murale and the Zn hyperaccumulator Thlaspi caerulescens - Elena Comino; Steven N. Whiting; Peter M. Neumann; Alan J. M. Baker (Plant and Soil, 2005)

Differential expression profiles of growth-related genes in the elongation zone of maize primary roots - Michal Bassani; Peter M. Neumann; Shimon Gepstein (Plant Molecular Biology, 2004)

The effect of Palamed G bone cement on early migration of tibial components in total knee arthroplasty - H. Kienapfel; R. Hildebrand; T. Neumann; R. Specht; M. Koller; I. Celik; H.H. Mueller; P. Griss; K.J. Klose; C. Georg (Inflammation Research, 2004)

RGD-mutants of B-lymphotropic polyomavirus capsids specifically bind to ?v?3 integrin - J. Langner; B. Neumann; S. L. Goodman; M. Pawlita (Archives of Virology, 2004)

Factors influencing long-term survival in mesothelioma patients?results of the German mesothelioma register - V. Neumann; A. Rtten; M. Scharmach; K.-M. Mller; M. Fischer (International Archives of Occupational and Environmental Health, 2004)

Further indications for genetic heterogeneity of euthyroid familial goiter - Susanne Neumann; Yvonne Bayer; Andreas Reske; Mria Tajtkov; Pavel Langer; Ralf Paschke (Journal of Molecular Medicine, 2003)

A technical note for using microsatellite DNA analyses in haploid male DNA pools of social Hymenoptera - R. F. A. Moritz; H. Scharpenberg; H. M. G. Lattorff; P. Neumann (Insectes Sociaux, 2003)

Lateral migrations of fishes between floodplain lakes and their drainage channels at the Lower Rhine: diel and seasonal aspects - J. Borcherding; M. Bauerfeld; D. Hintzen; D. Neumann (Journal of Fish Biology, 2002)
Although the total migratory activity of fishes from floodplain lakes in the Lower Rhine (Germany) into the connected drainage channels, estimated using electrofishing, fyke nets and visual observations, was low during summer 1997, conspicuous diel migrations of adult bream Abramis brama in June and July were recorded in one of the channels studied. A considerable proportion of the population of the floodplain lake immigrated into the channel at dusk and left it at dawn. During two winters (1994–1995, 1997–1998) the abundance of fishes increased considerably in the channels. The winter migrations, studied in detail in one of the channels in 1997–1998, started in late October, when the water temperature dropped below 10° C. In contrast to the mean of 500 fishes per 100 m channel length between May and October, >5000 fishes were found from November to March, with maximum values of >50 000 fishes per 100 m channel length in February 1998. More than 90% of these shoals were 0+ year fishes, dominated by roach Rutilus rutilus , bream, perch Perca fluviatilis and rudd Scardinius erythrophthalmus . These shoals entered the channel at sunrise and left it around sunset. Generally, the 0+ year fishes in the shoals swam separately from the older fishes, and different reactions towards the attack of predatory fishes were observed. The migrating shoals of juvenile fishes during the winter were interpreted as a strategy to minimize predation risk.

Effects of taurolidine and octreotide on port site and liver metastasis after laparoscopy in an animal model of pancreatic cancer - F.A. Wenger; M. Kilian; C. Braumann; A. Neumann; J. Ridders; F.J. Peter; H. Guski; C.A. Jacobi (Clinical & Experimental Metastasis, 2002)

Malignant mesothelioma - German mesothelioma register 1987-1999 - V. Neumann; S. Günther; K.-M. Müller; M. Fischer (International Archives of Occupational and Environmental Health, 2001)

Cereal/legume rotations affect chemical properties and biological activities in two West African soils - S. Alvey; M. Bagayoko; G. Neumann; A. Buerkert (Plant and Soil, 2001)

Characterization of a Series of Far Red Absorbing Perylene Diones: A New Class of Fluorescent Probes for Biological Applications - Nectarios Klonis; Huiqin Wang; Nurul H. Quazi; Joanne L. Casey; Gregory M. Neumann; Dean R. Hewish; Andrew B. Hughes; Les W. Deady; Leann Tilley (Journal of Fluorescence, 2001)

The theory of organism and the culturalist foundation of biology - Mathias Gutmann; Eva M. Neumann-Held (Theory in Biosciences, 2000)

Guest-editorial: “Organism” — Historical and philosophical issues - Mathias Gutmann; Eva M. Neumann-Held; Christoph Rehmann-Sutter (Theory in Biosciences, 2000)

Root-induced increases in soil pH and nutrient availability to field-grown cereals and legumes on acid sandy soils of Sudano-Sahelian West Africa - M. Bagayoko; S. Alvey; G. Neumann; A. Buerkert (Plant and Soil, 2000)

Cultivatable microbial biodiversity: gnawing at the Gordian knot - Brian J. Tindall; Evelyne Brambilla; Maike Steffen; Regine Neumann; Rüdiger Pukall; Reiner M. Kroppenstedt; Erko Stackebrandt (Environmental Microbiology, 2000)
Rapid and inexpensive sorting of bacterial isolates may be achieved using Fourier transform infrared spectroscopy (FT‐IR), a method that has hitherto been applied to identification and classification. The comprehensive characterization of environmental samples requires the isolation of large numbers of isolates using different growth media and growth conditions. In such cases, sorting the isolates is critical before isolates are subjected to more detailed studies. Using FT‐IR, isolates are grown under standardized conditions, and 100 strains can be tested within less than 8 h. Chemotaxonomic and molecular characterization of members of clusters emerging from FT‐IR analysis either at a level of spectral distance values below 20–30 (analysis of region 600–800 cm −1 , average linkage algorithm) or at spectral heterogeneity values below 75 (regions 1200–900, 3000–2798 and 901–698, scaling to first region, Ward's algorithm) reveals great similarities in fatty acids and 16S rDNA sequences. As judged from riboprinting analyses and fatty acid analyses, FT‐IR analysis is able to unravel intraspecific subclustering. The example used in this study of 100 isolates from a mat system, Lake Fryxell, Dry Valleys, Antarctica, selected from a larger number of isolates, picked mainly on the basis of colony pigmentation and form, reveals the utility of the method for identifying the number of putative species quickly. The method described is able to select strains rapidly that represent clusters at the specific and intraspecific level for subsequent characterization.

Characterization of a novel 21-kb deletion, CFTRdele2,3(21 kb), in the CFTR gene: a cystic fibrosis mutation of Slavic origin common in Central and East Europe - T. Dörk; M. Macek Jr; F. Mekus; B. Tümmler; J. Tzountzouris; T. Casals; A. Krebsová; M. Koudová; I. Sakmaryová; M. Macek Sr; V. Vávrová; D. Zemková; et al. (Human Genetics, 2000)

ETn insertion in the mouse Adcy1 gene: transcriptional and phylogenetic analyses - Wey L. Leong; Melanie J. Dobson; John M. Logsdon, Jr.; Raja M. Abdel-Majid; Leonard C. Schalkwyk; Duane L. Guernsey; Paul E. Neumann (Mammalian Genome, 2000)

The influence of cytochrome P450 1A1 and glutathione S-transferase M1 genotypes on biomarker levels in coke-oven workers - G. Brescia; L. Celotti; E. Clonfero; H. G. Neumann; A. Forni; V. Foà; M. Pisoni; G. M. Ferri; G. Assennato (Archives of Toxicology, 1999)

Is bradykinin a mediator of renal neuropeptide Y effects? - A. Bischoff; A. Neumann; A. Dendorfer; M. C. Michel (Pflügers Archiv - European Journal of Physiology, 1999)

Is bradykinin a mediator of renal neuropeptide Y effects? - A. Bischoff; A. Neumann; A. Dendorfer; M. C. Michel (Pflügers Archiv - European Journal of Physiology, 1999)

The Bereznjakovskoje gold trend, southern Urals, Russia - B. Lehmann; J. Heinhorst; U. Hein; M. Neumann; J. D. Weisser; V. Fedesejev (Mineralium Deposita, 1999)

Effects of climatic variability on the annual carbon sequestration by a boreal aspen forest - W. J. Chen; T. A. Black; P. C. Yang; A. G. Barr; H. H. Neumann; Z. Nesic; P. D. Blanken; M. D. Novak; J. Eley; R. J. Ketler; R. Cuenca (Global Change Biology, 1999)
To evaluate the carbon budget of a boreal deciduous forest, we measured CO 2 fluxes using the eddy covariance technique above an old aspen (OA) forest in Prince Albert National Park, Saskatchewan, Canada, in 1994 and 1996 as part of the Boreal Ecosystem‐Atmosphere Study (BOREAS). We found that the OA forest is a strong carbon sink sequestering 200 ± 30 and 130 ± 30 g C m –2 y –1 in 1994 and 1996, respectively. These measurements were 16–45% lower than an inventory result that the mean carbon increment was about 240 g C m –2 y –1 between 1919 and 1994, mainly due to the advanced age of the stand at the time of eddy covariance measurements. Assuming these rates to be representative of Canadian boreal deciduous forests (area ≈ 3 × 10 5 km 2 ), it is likely they can sequester 40–60 Tg C y –1 , which is 2–3% of the missing global carbon sink. The difference in carbon sequestration by the OA forest between 1994 and 1996 was mainly caused by the difference in leaf emergence date. The monthly mean air temperature during March–May 1994, was 4.8 °C higher than in 1996, resulting in leaf emergence being 18–24 days earlier in 1994 than 1996. The warm spring and early leaf emergence in 1994 enabled the aspen forest to exploit the long days and high solar irradiance of mid‐to‐late spring. In contrast, the 1996 OA growing season included only 32 days before the summer solstice. The earlier leaf emergence in 1994 resulted 16% more absorbed photosynthetically active radiation and a 90 g C m –2 y –1 increase in photosynthesis than 1996. The concomitant increase in respiration in the warmer year (1994) was only 20 g C m –2 y –1 . These results show that an important control on carbon sequestration by boreal deciduous forests is spring temperature, via the influence of air temperature on the timing of leaf emergence.

Dodecylphosphocholine micelles as a membrane-like environment: new results from NMR relaxation and paramagnetic relaxation enhancement analysis - Veronica Beswick; Raphaël Guerois; Françoise Cordier-Ochsenbein; Yves-Marie Coïc; Tam Huynh-Dinh; Jean Tostain; Jean-Pierre Noël; Alain Sanson; J.-M. Neumann (European Biophysics Journal, 1998)

Muscarinic-cholinoceptor mediated attenuation of phospholamban phosphorylation induced by inhibition of phosphodiesterase in ventricular cardiomyocytes: Evidence against a cAMP- dependent effect - Ramesh C. Gupta; Joachim Neumann; August M. Watanabe; Hani N. Sabbah1 (Molecular and Cellular Biochemistry, 1998)

Turbulent Flux Measurements Above and Below the Overstory of a Boreal Aspen Forest - P.D. Blanken; T. A. Black; H. H. Neumann; G. Den Hartog; P. C. Yang; Z. Nesic; R. Staebler; W. Chen; M. D. Novak (Boundary-Layer Meteorology, 1998)

Nestmate recognition and the genetic relatedness of nests in the ant Formica pratensis - M. Beye; P. Neumann; M. Chapuisat; P. Pamilo; R. F. A. Moritz (Behavioral Ecology and Sociobiology, 1998)

Nestmate recognition and the genetic gestalt in the mound-building ant Formica polyctena - M. Beye; P. Neumann; R.F.A. Moritz (Insectes Sociaux, 1997)

Productive expression state confers resistance of human immunodeficiency virus (HIV)-2-infected lymphoma cells against superinfection by HIV-1 - G. K. von Dalnok; Andrea Kleinschmidt; M. Neumann; Christine Leib-Moesch; V. Erfle; Ruth Brack-Werner (Archives of Virology, 1993)

Colonization of adrenal glands and ovaries of mice by variants of HSV 1 and 2 - H. Wiegand; H. P. Dienes; P. Schirmacher; J. Podlech; K. Bohl; M. Bohle; D. Neumann-Haefelin; D. Falke (Archives of Virology, 1991)

Structural analysis of proviral DNA in simian foamy virus (LK-3)-infected cells - M. Schweizer; R. Renne; D. Neumann-Haefelin (Archives of Virology, 1989)

Is there any influence of magnetic or astrophysical fields on the circadian rhythm of honeybees? - M. F. Neumann (Behavioral Ecology and Sociobiology, 1988)

Tomographic myocardial perfusion imaging using a hybrid time-modulated coded-aperture collimator system - Donald Richard Neumann; Yau Hwang Lee; Gerald M. Burma (Annals of Biomedical Engineering, 1988)

Heterogeneity of primate foamy virus genomes - M. Schweizer; Brigitte Corsten; D. Neumann-Haefelin (Archives of Virology, 1988)

A clonal analysis of Neisseria meningitidis serogroup A - B. A. Crowe; T. Olyhoek; B. Neumann; B. Wall; M. Hassan-King; B. Greenwood; M. Achtman (Antonie van Leeuwenhoek, 1987)

Metabolic activation of diethylstilbestrol and aminostilbene-derivatives - H. -G. Neumann; M. Metzler; W. Tpner (Archives of Toxicology, 1977)

Malate dismutation by Desulfovibrio - J. D. A. Miller; P. M. Neumann; Lynette Elford; D. S. Wakerley (Archives of Microbiology, 1970)